Tradisi Papajar dan Tradisi Munggahan dalam Perspektif Sosio–Kultural Masyarakat Cianjur - Dini Siti Rahmawati; Justika Ainun Mufti; Muhamad Parhan (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Indonesia, with its multicultural society, has many traditions/cultures, including Muslims when the Holy Month of Ramadan comes. Muslims in each region have diverse traditions. This includes Cianjur people who have papajar and munggahan traditions. Papajar tradition is the one usually held today by going on excursions and eating together with the family to tourist attractions which is carried out one or two weeks before the month of Ramadan. Meanwhile, munggahan tradition is carried out in Cianjur community by gathering with family and relatives, botram or eating together, forgiving each other, praying, visiting graves which is done one or two days before the month of Ramadan. This research aims to understand values, beliefs and cultural practices underlying papajar and munggahan traditions. This research uses qualitative literature study methods from book, previous research and internet sources. What will be examined in this research are papajar tradition and munggahan tradition in welcoming the holy month of Ramadan from the socio-cultural perspective of the Cianjur community. The result of research shows that papajar and munggahan traditions are two of many traditions commonly carried out by Cianjur people, and in practice these two traditions essentially contain mutual cooperation, solidarity, tolerance, order and togetherness.